2019
DOI: 10.1021/acs.orglett.9b01383
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Biosynthesis of Azabicyclene, a Conserved Nonribosomal Peptide in Pseudomonas aeruginosa

Abstract: Azabicyclene, an azetidine-containing natural product, was identified using quorum-sensing molecules to upregulate expression of a gene cluster highly conserved in the human pathogen Pseudomonas aeruginosa. Mutational studies of the gene cluster revealed essential genes for biosynthesis, including an unusual nonribosomal peptide synthetase. Reconstitution of this enzyme in vitro identified key biosynthetic intermediates. This work demonstrates a useful strategy for discovering quorum-sensing-regulated natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…P. aeruginosa LMG 1272 carries homologues of pyocin genes S4 and S11 and also a homologue of F-type tailocin gene cluster (10). Genome analysis using antiSMASH 5.0 (11) to identify biosynthetic gene clusters of secondary metabolites revealed the capacity to produce pyoluteorin (12), pyochelin (13), 2-amino-4-methoxy-trans-3butenoic acid (14), and azabicyclene (15). The lack of characteristic CLP biosynthetic genes (16) indicates that a different diffusible factor is involved in the WLR phenotype.…”
mentioning
confidence: 99%
“…P. aeruginosa LMG 1272 carries homologues of pyocin genes S4 and S11 and also a homologue of F-type tailocin gene cluster (10). Genome analysis using antiSMASH 5.0 (11) to identify biosynthetic gene clusters of secondary metabolites revealed the capacity to produce pyoluteorin (12), pyochelin (13), 2-amino-4-methoxy-trans-3butenoic acid (14), and azabicyclene (15). The lack of characteristic CLP biosynthetic genes (16) indicates that a different diffusible factor is involved in the WLR phenotype.…”
mentioning
confidence: 99%
“…Although only two peptide bonds are present in 6,t hree condensation domains were observed, suggesting that some of these Cdomains may be involved in unconventional processes.Phylogenetic analysis of Cdomains [23] revealed that, while AlbA-C 1 is an ormaL L-amino acid condensation domain, AlbB-C 2 and C 3 belong to au nique group of C* domains which are also found in the biosynthetic pathways of NPs, such as methoxyvinylglycine, [9] legonmycin, [24] azabicyclene, [8] puwainaphycin, [25] FK228, [26] bleomycin, [27] hassallidin, [28] nodularin [29] and microcystin [30] (Figure 4B). All of these NPs contain either dhAA motifs or motifs derived from dhAA residues.…”
Section: Identification Of the Biosynthetic Gene Cluster Ofmentioning
confidence: 99%
“…[4] Although less common, Dha and Dhb motifs do appear in non-ribosomal peptides (NRPs). Fore xample,t hey are present in the cyclic pentadepsipeptide,p homalide 1, [5] the cycloheptapeptide,[D-Asp 3 ,(Z)-Dhb 7 ]microcystin 2, [6] the blactam antibiotic norcardicin 3, [7] thep yrrolizidine alkaloid azabicyclene 4 [8] and the nonproteinogenic amino acid methoxyvinylglycine 5 [9] ( Figure 1A). In contrast to RiPPs, both (Z)-and (E)-Dhb geometries have been found in NRPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, no hydroxyl congeners were reported for pyrrolixenamides, lipocyclocarbamates, azetidomonamides or azabicyclene. 34 Taken together, the BMVOs involved in bacterial pyrrolizdine biosynthesis might only involve a remarkable three-step cascade reaction, and the final hydroxylation reaction catalyzed by LgnC might be an exception. 18 Compounds 6 and 7 would be produced by air-oxidation of 5ʹ.…”
mentioning
confidence: 99%